HUBUNGAN RISIKO LINGKUNGAN RUMAH DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BALITA DI UNIT PELAKSANA TEKNIS DAERAH PUSKESMAS FIDITAN KOTA TUAL - Raudhah Rettob; Bazrul Makatita (Pasapua Health Journal, 2019)
Introduction : Acute respiratory tract infection is a condition where in the last 2 weeks toddlers experience signs and symptoms such as coughing, runny nose, fever, nasal congestion, difficulty in drinking water, hoarseness or hoarseness, shortness of breath, appearing weak, and pulse fast as well as itchy or sore throat. Methode : analytic survey with cross sectional approach. The population is all mothers who have toddlers registered for treatment at the Regional Technical Implementation Unit of the Fiditan Community Health Center. Sampling uses a total sampling technique. The number of samples was 61 people. Result : there is a relationship between smoking habits of family members with the incidence of ARI in children under five with a value of p = 0,000 and there is a relationship between the habit of using mosquito coils with ARI in children under five with a value of p = 0,000. Conclusion : there is a relationship between smoking habits of family members with the incidence of acute respiratory infections in infants and there is a relationship between the habit of using mosquito coils with the incidence of acute respiratory infections in infants.